2021
DOI: 10.1177/15266028211058683
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline and Postprocedural Intravascular Ultrasound Findings on 1-Year Primary Patency After Drug-Coated Balloon Treatment of Femoropopliteal Lesions

Abstract: Purpose: Drug-coated balloons (DCBs) are commonly used for endovascular treatment of femoropopliteal lesions. Here, we employed intravascular ultrasound (IVUS) to investigate the predictors of restenosis after DCB treatment. Methods: This retrospective and single-center study was performed to examine 1-year primary patency after DCB treatment and to identify the risk factors for restenosis by analyzing clinical characteristics, angiographic findings, and IVUS measurements. We included 111 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…This report recommended a minimal lumen area ≥12.7 mm 2. 27 The use of IVUS might help in the selection of DCBs with diameters larger than the angiographically measured vessel diameter, which may have contributed to the reduction of residual stenosis. In the future, it is necessary to investigate the IVUS parameters associated with restenosis risk.…”
Section: Discussionmentioning
confidence: 99%
“…This report recommended a minimal lumen area ≥12.7 mm 2. 27 The use of IVUS might help in the selection of DCBs with diameters larger than the angiographically measured vessel diameter, which may have contributed to the reduction of residual stenosis. In the future, it is necessary to investigate the IVUS parameters associated with restenosis risk.…”
Section: Discussionmentioning
confidence: 99%
“…Few large-scale studies have investigated whether postprocedural findings could be associated with restenosis risk after DCB treatment. The restenosis after DCB treatment has been reportedly affected by various factors, including vessel diameter, CTO, and severe calcification [13][14][15] . The MLA was expected to be highly dependent on baseline characteristics, and the present study successfully addressed those confounding influences by using the GPS method.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IVUS-guided intervention has become a standard strategy in percutaneous revascularization of peripheral arteries as well as coronary intervention, especially in Japan [10][11][12][13] . A previous single-center registry showed that a larger IVUS-measured minimum lumen area (MLA) after DCB treatment was associated with a lower restenosis rate 14) . This association implies the effectiveness of larger lumen gain on primary patency after DCB treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Achievement of su cient luminal gain and less severe dissection are essential. Regarding the de nition of "su cient" luminal gain, Horie et al proposed a cutoff value of postprocedural IVUS-evaluated minimum luminal area (MLA) of 12.7 mm 2(Horie et al, 2022). Angiographic evaluation is the gold standard for the evaluation of dissection.…”
mentioning
confidence: 99%